4.2 Variation in Beta Defensin 1 Genotype is Associated with Preterm Birth. (26th April 2013) - James, CP; Bajaj-Elliott, M; Syngelaki, A; Klein, N; Nicolaides, K; Peebles, D
Abstract : Introduction: Human beta defensin 1 (HBD1) is an antimicrobial and immunomodulatory peptide present in cervical mucus. Variation in cervical antimicrobial expression is associated with preterm labour. We hypothesised that SNPs in the HBD1 gene may be associated with preterm birth. Methods: This is a retrospective case control study using blood collected at 11–13 weeks from women attending King's College Hospital March 2006-September 2010. 50 women with PPROM and 50 with spontaneous preterm labour were matched with 300 who delivered >37/40. SNPs rs1799946 (5′UTR) and rs1047031 (3′UTR) were genotyped by KASP assay (Kompetitive Allele Specific PCR, KBioscience). Data were analysed using multiplicative (rs1047031) and recessive (rs1799946) models and Chi Square Test. Results: There was no difference in BMI, smoking status or ethnicity between groups. Genotyping was successful in 98% (n = 390) and 97% (n = 386) samples for rs1047031 and rs1799946 respectively. Allele distribution demonstrated Hardy-Weinberg equilibrium. AA-homozygotes (rs1799946) had increased risk of PPROM; OR 2.24 (95%CI 1.11–4.49), p = 0.0.0257. 117 women had at least one prior delivery <37/40, 36 had a history of delivery <28/40. AA-homozygotes (rs1799946) had increased risk of delivery <37/40; OR 2.14 (95%CI 1.24–3.68), p = 0.005 and <28/40; OR 4.08 (95%CI 1.93–8.63), p < 0.0001. A allele carriers (rs1047031) were less likely to deliver <28/40; OR 0.288 (95%CI 0.121–0.683), p = 0.003. Conclusion: rs1799946 is associated with PPROM, a doubled risk of delivery <37/40 and a four-fold increase in the risk of delivery <28/40. rs1047031 may be protective. Variation in immune genotype may contribute to the clinical phenotype of women who deliver preterm.